Countering fraud for competitive advantage : the professional approach to reducing the last great hidden cost - Button, Mark , 1969-; Gee, Jim , 1957- (John Wiley and Sons, 2013)
Substantially reduce the largely hidden cost of fraud, and reap a new competitive advantage. As the title suggests, Countering Fraud for Competitive Advantage presents a compelling business case for investing in anti-fraud measures to counter financial crime